UPAYA PENINGKATAN KECAKAPAN HIDUP PESERTA DIDIK PAKET C MELAUI PELATIHAN PENGOLAHAN LIMBAH KAYU - Susilawati, Wina; Rukanda, Nandang; Rakhman, Anita (Comm-Edu (Community Education Journal), 2024)
This research aims to examine the effectiveness of wood waste processing training in fostering entrepreneurial spirit among students in Package C. The training methods employed include lectures, discussions, and hands-on practices in wood waste processing. The research sample consists of 20 students in Package C who have an interest in enhancing their skills through wood waste processing. This study utilizes a qualitative descriptive method. Data were collected through interviews and documentation observation to measure knowledge of wood waste processing, entrepreneurial attitudes, and entrepreneurial intentions. The results of the research indicate that wood waste processing training significantly enhances students' knowledge of wood waste processing. Furthermore, the training also has a positive impact on students' entrepreneurial attitudes, as evidenced by a significant improvement in proactive attitudes, initiative, and opportunity orientation. Additionally, the training significantly influences students' entrepreneurial intentions. These findings suggest that wood waste processing training is effective in cultivating entrepreneurial spirit among students in Package C. The implications of this research underscore the importance of integrating entrepreneurship training into the Package C curriculum to provide students with relevant skills and knowledge in wood waste processing.